Archaea membranes in response to extreme acidic environments - Chong, Parkson Lee-Gau (Frontiers in Biophysics, 2024)
Bipolar tetraether lipids (BTL), such as glycerol dialkyl calditol tetraether (GDNT) and glycerol dialkyl glycerol tetraether (GDGT), are the dominating lipid species in thermoacidophiles that inhabit at pH ≤ 4 and temperatures ≥ 65C. BTL containing archaea membranes respond to environmental pH changes by varying the number of cyclopentane rings in the isoprenoids, the amount of GDNT relative to GDGT, the ratio of tetraethers to diethers, and the level of glycosylation in polar headgroups. These structural and compositional adjustments can alter the hydrogen bond networks in the membrane polar headgroup regions and the packing tightness and rigidity in the membrane hydrophobic core. It is likely that these changes in non-covalent interactions among archaea lipids are made to retain low membrane volume fluctuations and their low sensitivity to temperature, as illustrated in the case of liposomes made of the polar lipid fraction E (PLFE) of Sulfolobus acidocaldarius. As such, a low passive proton permeability and a near neutral intracellular pH can be maintained, and, as a result, optimal activities of soluble and membrane-bound proteins in thermoacidophiles can be retained in acidic growth conditions at elevated growth temperatures.